High-affinity alpha-thrombin binding to platelet glycoprotein Ib alpha: identification of two binding domains. - Gralnick, H R (1994)
alpha-Thrombin binding to and activation of platelets are of major importance in the initiation of physiologic thrombi and in the genesis of arterial thrombus formation. We have studied the site(s) and affinity of thrombin binding to human platelets. Our studies of the peptide inhibition of thrombin binding indicate that the glycoprotein Ib alpha binding site is of high affinity, Kd approximately 10(-10) M, while the seven-transmembrane-domain site is a moderate-affinity thrombin binding site, Kd approximately 10(-8) M. Further studies to modulate the high- or moderate-affinity thrombin binding can be directed to a specific class of sites. This would allow partial or total inhibition of specific thrombin-platelet interaction(s) in different clinical settings.